2021
DOI: 10.4269/ajtmh.20-1330
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Parenchymal and Subarachnoid Neurocysticercosis

Abstract: Abstract.Neurocysticercosis (NCC) is endemic in many parts of the world, carrying significant neurological morbidity that varies according to whether lesions are located inside the cerebral parenchyma or in extraparenchymal spaces. The latter, in particular subarachnoid NCC, is assumed to be more severe, but no controlled studies comparing mortality between types of NCC exist. The aim of this study was to compare all-cause mortality between patients with intraparenchymal NCC and those with subarachnoid NCC. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…It is associated with hydrocephalus and intracranial hypertension and results in high mortality rates if not recognized and treated appropriately. 11 We used urine from patients with subarachnoid NCC for the initial testing phase of this prototype dipstick because of the consistently high levels of parasite antigens characteristic of subarachnoid NCC. Clearly, this preliminary series does not assess the performance of the test in other types of NCC, such as parenchymal NCC, in which antigen levels may be much lower and test sensitivity could decrease significantly.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with hydrocephalus and intracranial hypertension and results in high mortality rates if not recognized and treated appropriately. 11 We used urine from patients with subarachnoid NCC for the initial testing phase of this prototype dipstick because of the consistently high levels of parasite antigens characteristic of subarachnoid NCC. Clearly, this preliminary series does not assess the performance of the test in other types of NCC, such as parenchymal NCC, in which antigen levels may be much lower and test sensitivity could decrease significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent and protracted disease in the racemose/subarachnoid phenotype and the unreliability in following clinical and radiologic changes [ 2 ]. Despite the high morbidity [ 11 ] and mortality [ 12 ] reported in this patient population, our group has previously demonstrated the utility of using a comparator assay to determine durable cure, which enables the safe discontinuation of treatment [ 13 ]. Here we demonstrate that TsG10-TsG10*bt was 95% sensitive in the serum and 100% sensitive in the CSF in detecting active extra-parenchymal disease in our patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Subarachnoid NCC represents the most lethal form of NCC. In a study of 840 NCC patients seen at the National Institute of Neurological Sciences in Peru, Abanto et al [11] identified 42 deaths. Most deaths were among the minority with subarachnoid NCC (32/193, 16.6% of subarachnoid cases).…”
Section: Treatment Approachmentioning
confidence: 99%
“…Subarachnoid NCC is considered the most severe form of disease and carries the highest mortality rates [11,12 ▪▪ ]. Enlarging cysts can cause mass effect and focal deficits.…”
Section: Clinical Presentationmentioning
confidence: 99%